Localized bullous pemphigoid: Four clinical cases and a literature review - Chloe Algoet; Sabine Mostinckx; Ivan Theate; Olivier Vanhooteghem (Clinical Case Reports, 2020)
Abstract Localized bullous pemphigoid (LBP) rarely evolves into the generalized form, and the prognosis is better. In our opinion, the occurrence of LBP is underestimated because of incorrect diagnoses. It is therefore important to perform a skin biopsy each time a bullous rash is concerned in order to make a definite diagnosis.